Analisis Legalitas Perparkiran di Kota Gorontalo - Sharul Ramadhan, Aditya (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
In accodance Article 27 paragraph (1) of the 1945 Constitution, of republic of Indonesia, it is affirmed that “all citizens shall have equal status before the law and government and shall be obliged torespect the law and government without exception." Parking managers and parking users have the same position before the law, therefore they are obliged to respect each other's rights and obligations. The purpose of this research is to empirically analyze the legality of parking in Gorontalo City. The research method uses a qualitative descriptive type. This study empirically analyzes the legality of parking in Gorontalo City. The research method used is descriptive qualitative. The results show that on almost all public roads in Gorontalo City, especially in busy areas, there are illegal parking attendants. The findings indicate that in nearly all public roads throughout Gorontalo City—particularly in areas with high public traffic—the parking activities are carried out by attendants whose legal status is questionable. These individuals do not possess formal identification as mandated under Regional Regulation of Gorontalo City Number 2 of 2019 on Parking Management. Article 8 paragraph (5) of said regulation clearly stipulates that any individual conducting parking attendant duties must be appointed by the Mayor of Gorontalo and be equipped with an official Letter of Assignment and Identification Card. However, Article 9 paragraph (4) of the regulation highlights that many parking attendants operate without issuing payment receipts or parking tickets to users, which constitutes a failure to provide legally recognized proof of payment. As a result, this undermines legal certainty and consumer protection regarding parking payments made to parking operators